(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Precision design for a basin solar still is frequently out of reach. This problem is resolved by coating the basin area with a nanolayer that enables stimulation and control of the complex rate of physiognomies evaporation. Here, a physical-scale action has developed a solar still to absorb energy quickly. The consistent occurrence over a time series of dynamics transfer from the basin liner to the salt water determines how well the solar still performs. When compared to an SBSS coating made of SiO2 or TiO2, and/or coatings without nanoparticles, it is similar higher. The binary search tree made it possible to determine the solar system’s best price while it was still being researched and to create a better design with better performance.